STUDENTS’ PERSPECTIVES ON PEER ASSESSMENT - Hamdiyati; Sukri Adani (Nusantara Hasana Journal, 2023)
This study aims to explore the student perspectives on peer assessment application in their context. The instrument used in this study was a semi-structured interview which contained 4 general questions asking about the student’s opinions on the application of peer assessment that had been carried out in class. The research employed a descriptive qualitative method by interviewing 15 students of STKIP Muhammadiyah of Southwest Aceh. The results of the interviews were then transcribed and grouped into four sections according to the questions asked, namely: knowledge/literacy, implementation techniques, benefits, goals and challenges, trust. The results of the analysis indicate that peer assessment is effectively carried out in the classroom seen from the results of the interviews.